The Challenge of Lorazepam Failure: Malignant Catatonia Treated Successfully with Valproate - J. Kim; E. Garrels; A. Zamiri; K. Tran; A. Francis (European Psychiatry, 2024)
Introduction Despite the unclear nature of catatonia, the treatment response of catatonia to benzodiazepines is widely known for its typical, dramatic recovery. The neurobiological correlates of this phenomenon regarding specific receptors and neurotransmitters are unclear, as are the potential treatment options. This is important to consider when the most commonly recommended treatments of catatonia with Lorazepam or Electroconvulsive Therapy (ECT) are unavailable or unsuccessful. In this report, we describe a case of severe, malignant catatonia and psychosis mostly unresponsive to Lorazepam during two different hospitalizations, but with eventual return to baseline after successful treatment with Valproate.